2010
DOI: 10.1128/aem.01169-10
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella entericain Commercial Swine Feed and Subsequent Isolation of Phenotypically and Genotypically Related Strains from Fecal Samples

Abstract: The purpose of this study was to determine the occurrence and genotypic relatedness of Salmonella enterica isolates recovered from feed and fecal samples in commercial swine production units. Of 275 feed samples, Salmonella was detected in 10 feed samples that originated from 8 of 36 (22.2%) barns, with a prevalence of 3.6% (10/275 samples). In fecal samples, a prevalence of 17.2% was found at the early finishing stage (1,180/6,880 samples), with a significant reduction in prevalence (7.4%) when pigs reached m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 22 publications
6
45
0
Order By: Relevance
“…Thirteen of these first isolations were made only from human and 34 only from non-human sources. Five serovars, namely Salmonella Mississippi, Salmonella Hvittingfoss, Salmonella Isaszeg, Salmonella Lindern and Salmonella IV (11:z 4 ,z 24 :−) were isolated from both sources. The biochemical behaviour of all the strains was regular and Salmonella enterica subsp.…”
Section: Results and Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen of these first isolations were made only from human and 34 only from non-human sources. Five serovars, namely Salmonella Mississippi, Salmonella Hvittingfoss, Salmonella Isaszeg, Salmonella Lindern and Salmonella IV (11:z 4 ,z 24 :−) were isolated from both sources. The biochemical behaviour of all the strains was regular and Salmonella enterica subsp.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Animal feed is a recognized source of pathogenic microorganisms for animals [16]. It is still relatively common to find evidence of contamination of domestic and imported feed and animal-feed ingredients [17][18][19][20][21][22][23][24][25][26]. Salmonella can be isolated regularly from feedstuffs and feed ingredients, including both animal and vegetable proteins, such as soya, rape, palm kernel, rice bran and cottonseed.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Pig fecal samples were from a major time-nested longitudinal study of Salmonella infection in finisher pigs (32). Three different vertically integrated commercial swine production systems (BC1 to -3), located in North Carolina, were sampled during March to November 2009 and resulted in a total of 1,874 pig fecal specimens across all systems (see Table S1 in the supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Mohammed et al (2009) found twice the incidence of L. monocytogenes in drinking troughs, feeders and cow beds (66%, 65%, and 55%, respectively) than in silage (30%). Although pathogen control procedures such as heat treatment or the addition of chemicals can be used in the feed manufacturing process, Molla et al (2010) strongly question the conventional wisdom that processed feed is not a source of bacterial contamination.…”
Section: Listeria Monocytogenes In Dairy Cow Feed Diet and Faecal Shementioning
confidence: 99%